ONLINE BUSINESS TRANSFORMATION IN THE COVID-19 PANDEMIC ERA (CASE STUDY OF MSME ACTIVITIES IN TANGERANG CITY) - Annisa Putri Auliya; Elang Rizka Syah Putra; Sandra Puspa Dewi; Zahirah Khairunnisa; Mohammad Sofyan; Fifin Arifianti; Nur Fitri Rahmawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to find out how the online business transformation in Micro, Small and Medium Enterprises (MSMEs) during the Covid-19 pandemic. The Covid-19 pandemic has made the majority of economic sectors, especially MSMEs stagnant. The majority of MSME actors cannot develop and many end up in bankruptcy. This is what makes MSME business actors change their sales strategy through digitalization schemes. The digitization scheme is by utilizing a marketplace (intermediary) and using social media as a marketing technique. In addition, digital MSME actors must be able to synergize with netizens in marketing products and services. Thus, the digital MSME development scheme can be an alternative to saving business actors in the midst of the Covid-19 pandemic. This research uses descriptive qualitative method. The formulation of the problem in the research is: how MSMEs adapt to the online business transformation in the era of the Covid-19 pandemic, the impact of MSME turnover on the Covid-19 pandemic, and how big the impact of the COVID-19 The pandemic is on the MSME workforce. This study argues that the development of digital MSMEs has become an alternative to saving as well as developing digital entrepreneurship in Indonesia during the Covid-19 pandemic